2021
DOI: 10.1590/1984-0462/2021/39/2020046
|View full text |Cite
|
Sign up to set email alerts
|

Anthropometric and Dietary Assessment of Patients With Glycogenosis Type I

Abstract: Objective: To perform anthropometric and dietary evaluation of patients with glycogenosis type Ia and Ib. Methods: This cross-sectional study is composed of a sample of 11 patients with glycogenosis divided into two subgroups according to the classification of glycogenosis (type Ia=5 and type Ib=6), aged between 4 and 20 years. The analyzed anthropometric variables were weight, height, body mass index, and measures of lean and fat body mass, which were compared with reference values. For dietary assessment,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…Other similar studies have shown 20-40% of patients with short stature. [38,39] Furthermore, we showed that adherence to treatment significantly improves height.…”
Section: Discussionmentioning
confidence: 84%
“…Other similar studies have shown 20-40% of patients with short stature. [38,39] Furthermore, we showed that adherence to treatment significantly improves height.…”
Section: Discussionmentioning
confidence: 84%
“…However, this may also be reflective of better acceptance and compliance of treatment in our cohort with improved access to local care. Only 1 patient (7%) had short stature which is less than other recently reported cohorts with an incidence between 20% and 40% 33,36,37 . The normal height in the majority of patients likely reflects the good metabolic control, which has previously been shown to improve growth 36 .…”
Section: Discussionmentioning
confidence: 62%
“…Only 1 patient (7%) had short stature which is less than other recently reported cohorts with an incidence between 20% and 40%. 33,36,37 The normal height in the majority of patients likely reflects the good metabolic control, which has previously been shown to improve growth. 36 Further no patients required continuous overnight feeds, there were no hospitalizations in the past 12 months due to a hypoglycemic complication, and no patients required liver transplant.…”
Section: Discussionmentioning
confidence: 97%